Rwanda Multi-Donor Civil Society Support Programme (2015-2021) - DFID (2018)
Project data for the Rwanda Multi-Donor Civil Society Support Programm e (2015-2021). Strengthened civil society engagement on critical socia l cohesion, reconciliation and governance issues in Rwanda. DFID will provide funding and technical support to Rwandan civil society organis ations to support the design and implementation of governance and reco nciliation focused initiatives, and to support more effective engageme nt (influencing) with government on these issues.